Elaboración de un manual de Buenas Prácticas de Manufactura (BPM) dentro de la microempresa “Heladería Skinny” ubicada en la parroquia Once de noviembre, en el cantón Latacunga. - Molina Zapata, Verónica Alexandra (2021)
Within the food industries, Good Manufacturing Practices (GMP) are characterized by linking safety, hygiene and quality through the production, distribution and marketing chain in order to obtain safe and healthy products for human consumption. The micro-business ‘Heladería Skinny’ is a food producer dedicated to the production of a variety of flavoured ice-creams. The aim of this research study was to bring knowledge and develop a manual of Good Manufacturing Practices (GMP), and its impact on product quality. To create the manual, the deductive and inductive methodology was applied by using a checklist based on good manufacturing practices for processed foods by the Agencia Nacional de Regulación, Control y Vigilancia Sanitaria ARCSA-DE-067-2015-GGG’, with the purpose of verifying the infrastructure, facilities and production operations. On the other hand, the types of research employed were revision of documents that helped in the collection of information through literature reviews and field research through an interview that resulted in information and real data which revealed a high level of LACK OF COMPLIANCE within the micro-business “Heladería Skinny” with 56% and a compliance of 37% in accordance with the non-compliance an improvement plan was established that included the creation of a good manufacturing processes manual and a budget of $2509.19 for changes to the facilities. A training timeline was established for personnel that will last 4 months, which seeks to share knowledge based on SOP (Standard Operating Procedures) and SOCP (Standard Operating Cleaning Procedures) with the purpose of increasing production capacity and the product quality.